Strategies for sustainable production of starch from sweet potato - Zulkifli, Nurul Ainina; Mohd Nor, Mohd Zuhair; Mokhtar, Mohd Noriznan; Sulaiman, Alifdalino (Malaysian Society of Agricultural Engineers, 2019)
Sweet potato (Ipomoea batatas L. Lam) belongs to the Convolvulaceae family. It is originated from southern Central America and can be easily grown in the tropical climax. The sweet potato contains high nutritional values such as carbohydrate, protein, dietary fibre, amino acids, enzymes, minerals, and vitamins. The main component in sweet potato is starch, which can be used in many food applications. The main objective of this study is to propose some strategies in designing a sustainable starch production from sweet potato. This can be done with the consideration of efficient starch production steps as well as the production of its by-products in order to minimize the wastes as well as to maximize the net profitability. The implementation of the recommended strategies in this study will hopefully ensure sustainable and feasible production of starch from sweet potato which can benefit the farmers and producers of this crop.